Maximum Optimal Asset Utilization in Overhead Transmission and Low Voltage Distribution Networks - Talpur, Saifal (Auckland University of Technology, 2020)
The growing trend towards renewable energy and e-mobility is behind the congestion in the overhead transmission and low voltage distribution networks. An effective approach towards minimizing the congestion in both networks is to operate the assets to their maximum but optimal utilization. An excessive but reliable electricity flow can minimize congestion, avoid load shedding and maintain reliability in the electricity network. In the transmission network, congestion across overhead transmission lines is obtained when loading them at their maximum rating, calculated under the assumed and worst weather conditions, thus resulting in bottlenecks and ultimately the limited line flows. The congestion in the distribution network is seen across distribution transformers, mainly in result of growing electric vehicles (EVs) charging load. Distribution transformers when rated under the worst weather conditions may exhibit underutilised loading capacity towards fulfilling the loading demand from EVs. Asset management in both networks moreover requires the ability of existing assets to transfer the required electricity flow at the minimum cost while attaining the maximum life by operating them to their maximum optimal physical limit. The concept of ‘maximum optimal asset utilization’ is related to operating the existing assets to their maximum but efficient loading capacity to maintain reliability and security with obtaining the minimized congestion and extended asset lifetime. It further assures that the asset operation complies with the design standards as well as addresses both electrical and thermal constraints. This thesis thus provides ‘maximum optimal asset utilization’ solution to transmission and distribution system operators to manage the asset loading in order to obtain maximum, reliable and efficient capacity utilization. The scope of the thesis is furthermore divided in two parts, where, the first part deals with maximum utilization of overhead transmission lines (OHLs) in the high voltage (HV) transmission network. To obtain the maximum optimal loading across OHLs, the hot-spots were identified with the help of the proposed technique to achieve the reliable line loading. The second part concentrates on obtaining the maximum capacity utilization across distribution transformers in the low voltage (LV) distribution network. The results indicated that the test DT achieved 25.9% more life with proposed technique under coordinated BEV charging and 51% more life under uncoordinated BEV charging.
Keywords: Overhead Line; Dynamic Line Rating; Asset Utilisation; Low Voltage Distribution Networks